South-East Asian Export Performance: External Market Access and Internal Supply Capacity. - Redding, S; Venables, A (2003)
This paper investigates the determinants of divergent export performance across countries and regions, focusing in particular on South-East Asia. We begin with a general decomposition of export growth into the contributions of increased external demand (foreign market access) and improvements in internal supply-side conditions (supply capacity). Foreign market access growth is shown to make a substantial contribution to explaining divergent export performance and to be highly geographically concentrated. Building on the results of the decomposition, we move on to an econometric analysis of the determinants of export performance, where we find important roles for external geography, internal geography and institutional quality.